An Overview of Tempeh as A Polyphenolic Cuisine in Javanese Well-being Practice - Tresya Yuliana Fitri (Pusat Unggulan Ipteks Javanologi Universitas Sebelas Maret, 2026)
This paper describes the Javanese well-being tradition through the example of culinary tradition of Wonogiri through daily Tempeh consumption. Tempeh is known to contain high polyphenolic compounds such as flavonoids as the largest class of polyphenol in the plant kingdom. This work also traces the well-being tradition through food history from the old translated scriptures and or inscriptions from the general mentions about food, including tempeh and the history of soybeans. However, the paper does not established the origins of fermentation skills in the old Javanese cuisine depicted by then alcoholic drink, and later by tempeh fermentation in the Serat Centhini. This work as well proposed and defined what constitutes polyophenolic cuisine and why cuisine of Wonogiri fulfils the requirement and the characteristics supported through the elaboration of Tempeh as the main ingredient which is central to the people’s diet in Wonogiri. The work also describes the theoretical aspects of the food compositions and its phytochemical such as Pyrroloquinoline quinone (PQQ), Coenzyme Q10, iron and copper balance, which may lead to the maintenance of general well being of the population.